Aspects of employment and remuneration before and after the crisis - Campos Tomcsányi, Zsuzsanna Rózsa (2020)
The component of labor, understood in this article as the work performed by individuals for companies, has shown a perceptible decline in conditions. The conditions of the working population and explanations for the causes of unemployment have been topics of discussion in various circles of historical thought. From the Great Depression on, the notion that unemployment is caused by the decisions of individuals who reject jobs available or payments offered has been put to question. The view on labor models and trends present in some economic currents of thought in the twentieth century is briefly presented, and some aspects that impact on the prevailing labor conditions in the economy are discussed.